1988
DOI: 10.1002/1097-4679(198809)44:5<691::aid-jclp2270440505>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Elements of death anxiety and meanings of death

Abstract: The objectives of this study were: (1) to test hypotheses that women would have higher death anxiety than men and that older persons would have lower death anxiety than younger people; and (2) to probe for meanings of death among a large, heterogeneous sample. A group of 599 adolescents and adults completed a death anxiety scale; factor analysis of the resultant data revealed seven orthogonal factors. Both hypotheses were supported at acceptable levels of significance. Item analysis revealed additional informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 56 publications
9
46
1
Order By: Relevance
“…However, men and women have been shown to construe fear of death differently (Lonetto & Templer, 1986) . Women, for example, seem to express higher fears of decomposition and the pain associated with dying (Diggory & Rothman , 1961;Thorson & Powell, 1990). Furthermore, it is not unusual for various personality measures to report separate norms for males and females.…”
Section: Resultssupporting
confidence: 86%
“…However, men and women have been shown to construe fear of death differently (Lonetto & Templer, 1986) . Women, for example, seem to express higher fears of decomposition and the pain associated with dying (Diggory & Rothman , 1961;Thorson & Powell, 1990). Furthermore, it is not unusual for various personality measures to report separate norms for males and females.…”
Section: Resultssupporting
confidence: 86%
“…Contrary to these findings, Thorson and Powell (1988) and Henrie and Hicks-Patrick (1970) found that the elderly experienced less death anxiety than younger individuals, since their conflict-resolving and anxiety-coping skills were better. Russac, Gatliff, Reece, and Spootswood (2007) investigated the relationship between death anxiety and the variables of age and gender in their study of 304 individuals (aged 18-87 years) living in the United States.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, in this study, levels of depression and trait anxiety were measured and their possible effects on death anxiety were examined. In addition, the effect of gender and age on death anxiety, which was demonstrated by previous studies (Cicirelli, 2001;Drolet, 1990;Galt & Hayslip, 1998;Rasmussen & Brems, 1996;Tang, Chiou, Lin, Wang, & Liand, 2011;Thorson & Powell, 1988), was also investigated.…”
Section: Introductionmentioning
confidence: 66%
“…This finding repeated the results of Cicirelli (2001) and Thorson and Powell (1988). In addition, women had higher general anxiety scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation